Mom's Knowledge and Practice on Prevention Pneumonia in Toddlers - Lindesi Yanti; Fermata Sari (GLOBAL HEALTH SCIENCE GROUP, 2022)
Children under five must get protection to prevent the occurrence of pneumonia which can result in impaired growth and development or can even result in death Objective: Therefore, mother's knowledge must be increased for the prevention of pneumonia Method: The research design used was a quasi-experimental approach with a one-group pretest-posttest design approach on 38 mothers of children under five. The sample technique used is probability sampling using simple random sampling technique. The research instrument used a questionnaire with 22 knowledge questions with Cronbach's absence (0.844) and action (0.826). Data analysis using paired t-test. Results: The results of statistical tests showed that knowledge (p-value = 0, 000) and action (p-value = 002). Conclusions It can be concluded that there is an average difference between knowledge and practice of mothers under five before and after being given material on prevention of pneumonia.